2008
DOI: 10.1136/gut.2007.142919
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference correlates with liver fibrosis in children with non-alcoholic steatohepatitis

Abstract: Abdominal rather than generalised obesity contributes to liver fibrosis in children with NAFLD. Waist is also the only component of the metabolic syndrome to be associated with fibrosis in these children. Therefore, the presence of abdominal obesity is an additional criterion for the selection of children and adolescents who should undergo extensive investigation, including liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 55 publications
(49 reference statements)
5
83
0
1
Order By: Relevance
“…The prevalence of NAFLD was increased according to the increase of BMI or abdominal circumference reported from Japan 24 . But other report concluded that waist circumference is an independent predictor of advance histological changes in NAFLD than BMI 25,26 . But waist circumference was similar in NASH and NNFL in our series.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of NAFLD was increased according to the increase of BMI or abdominal circumference reported from Japan 24 . But other report concluded that waist circumference is an independent predictor of advance histological changes in NAFLD than BMI 25,26 . But waist circumference was similar in NASH and NNFL in our series.…”
Section: Discussionmentioning
confidence: 96%
“…Noteworthy, in children with NAFLD [32], [33] and [34], waist circumference was the only component of the metabolic syndrome associated with liver fibrosis. It is possible that this reflects the lower number of confounding factors in pediatric patients, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The body mass index (BMI) and BMI Z-score were calculated according to established criteria (18,19). Metabolic syndrome was defined by the presence of three or more of the following five criteria: abdominal obesity (defined by waist circumference ≥90th percentile for age), hypertriglyceridemia (triglycerides >95th percentile for age, gender and race), low HDL cholesterol (HDL cholesterol <5th percentile for age and gender), elevated blood pressure (defined as systolic or diastolic blood pressure >95th percentile for age and gender), and impaired fasting glucose or known type 2 diabetes mellitus.…”
Section: Methodsmentioning
confidence: 99%